Social and family capital and youth career intension: A case study in Pakistan - Amjad Ali; Shafiqa Ahsan; Sophia F. Dziegielewski (Cogent Business & Management, 2017)
Selecting a career can be a complex decision for young adults in any country. Developing an entrepreneurial career choice can benefit a country and its people in many ways. This study examined the opinions of 200 university students that were business-related majors in Pakistan to determine the factors considered important for entrepreneurial growth. Previous research from across the globe was examined and related to this topic. In this study, examining social capital included family networks, professional and recreational networks and having entrepreneurial role models. When looking specifically at social capital, consistent with previous research conducted across the globe, all of the areas were found to be significant. Whereas, family capital (family size, father's occupation, father's income when related to career intention) were not found to be statistically relevant to the career choice. This relationship is examined, and these findings in Pakistan are compared to previous research, and recommendations for future research are made.
Keywords: 650